Left of forever : a novel - DeWitt, Tarah (St. Martin's Griffin, 2025)
"This time, they'll get it right. Wren and Ellis Byrd fell in love as kids, had their son Sam when they were only teenagers, and built a life together in the coastal town of Spunes, Oregon. They were made for one another . . . until they fell apart. Now divorced and in their 30s, Wren runs the bakery in town, while Ellis works as a firefighter. They live separate lives, though they are hardly off each other's minds. When Ellis and Wren move Sam into college, Ellis convinces Wren to take an extended road trip back to Spunes to see if they can give their relationship one last chance. Amid the gorgeous California coastline and the intimacy they have missed for years, Wren starts to think it just might be possible. But can the past truly be left behind? When words fail and old wounds resurface, it's a soul-baring letter that could finally reveal the truth-or close the door on them forever"--